(untitled) (Proceedings of Southern Federal University. Philology, 2018)
Natalya G. Burmakina (Krasnoyarsk, Russian Federation) The paper is aimed at the analysis of the discursive work on creating the self-credibility in academic communication. The genre of institutional personal page on the University sites is considered. The author describes the most frequent, in this genre, discursive practices of constructing credibility in Russian and Spanish. The method used in the research is critical discourse analysis. Key words: credibility, identity, academic discourse, personal page, discursive practice.